1979
DOI: 10.1159/000194054
|View full text |Cite
|
Sign up to set email alerts
|

Helium-Oxygen Flow Volume Curves in Young Healthy Adults

Abstract: Helium-oxygen (HeO2) flow volume curves were done in young, healthy, nonsmoking adults. This paper discusses the theoretical design of the test, the nomenclature, and the results in this population. Our study shows that HeO2 and air curves crossed around 15% of vital capacity; one point of identical flow occurs more frequently than has been appreciated; and fully developed laminar flow occurs infrequently at low lung volumes in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…In our analysis of density dependence, the FVC for the air and the helium-oxygen gas mixture were within 6%, similar to the reproducibility used in older subjects (4,5,8,13,18,19,25,32). We matched the two forced expiratory maneuvers at RV for comparison of flows and calculation of V iso V , a method of analysis that is similar to that used in older subjects (1,7,8,13,16,26,29). Rubinstein et al (28) demonstrated that the magnitude of density dependence was not significantly different whether the curves were matched at RV or total lung capacity.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our analysis of density dependence, the FVC for the air and the helium-oxygen gas mixture were within 6%, similar to the reproducibility used in older subjects (4,5,8,13,18,19,25,32). We matched the two forced expiratory maneuvers at RV for comparison of flows and calculation of V iso V , a method of analysis that is similar to that used in older subjects (1,7,8,13,16,26,29). Rubinstein et al (28) demonstrated that the magnitude of density dependence was not significantly different whether the curves were matched at RV or total lung capacity.…”
Section: Discussionsupporting
confidence: 77%
“…Although the methodology for obtaining maximal flows in sleeping infants differs from that used in cooperative older children and adults, our laboratory has previously demonstrated that flow limitation is achieved in healthy infants over the lower 50% of the FVC (10). In our analysis of density dependence, the FVC for the air and the helium-oxygen gas mixture were within 6%, similar to the reproducibility used in older subjects (4,5,8,13,18,19,25,32). We matched the two forced expiratory maneuvers at RV for comparison of flows and calculation of V iso V , a method of analysis that is similar to that used in older subjects (1,7,8,13,16,26,29).…”
Section: Discussionsupporting
confidence: 69%